Pemeliharaan Arsip di Kantor Pengadilan Tinggi Padang - Najaf, Febdia; Nst, Bakhtaruddin (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
The objective is to (1) describe the preservation and, (2) constraints encountered in the preservation of records at the office of the High Court of Padang and solutions. Data were collected through observation and interviews with archivists at the Office of the High Court of Padang. Analyzing the data be descriptive. Analyzing data can be summarized as follows. Preservation of records has not been performing well due to the cleaning room archives still using manual and preservation manual does not have archives so that causes some archives to accumulate and not preservation. And constraints faced by the state of the room and facilities are still very simple, a small office to a large volume of records that can not accommodate the archive files created causing overlap. In addition, the number of archivists are still lacking in the field.